Allelic polymorphisms of thymidylate synthase gene and their haplotypes as predictors of the therapeutic response to methotrexate in patients with rheumatoid arthritis - I. V. Devald; E. A. Khodus; E. B. Khromova; O. B. Nesmeyanova; A. L. Burmistrova (Научно-практическая ревматология, 2019)
Methotrexate (MT) is recognized as the main component of the treat to target strategy in patients with rheumatoid arthritis (RA). Unfortunately, MT therapy is not equally effective in all patients with RA, some of them are resistant to such treatment, and have steady progression of destructive changes of the joints, reducing quality of life and leading to disability.Objective: examination of genetic predictors of therapeutic efficacy and resistance to MT among single-nucleotide polymorphisms (SNP) of folate cycle genes, in particular polymorphisms of the thymidylate synthase gene TSER 2R/3R and TS 6bp del/ins and their haplotypes.Subjects and methods. The study included 85 patients with RA, who were prescribed MT at a dose of 10 to 17.5 mg/week as a the «first line» disease-modifying antirheumatic drug. The therapeutic response was evaluated with DAS28 after 6 months of continuous treatment. According to the results of this assessment groups of «respondents» and «non-respondents» to MT were identified. Genetic typing of SNP TSER 2R/3R and TS 6bp del/ins was performed by real-time polymerase chain reaction.Results and discussion. In RA patients with different efficacy of MT, statistically significant differences in the frequency of alleles and genotypes of polymorphic variants of the gene thymidylate synthase were revealed. Thus, in patients resistant to MT homozygous genotype TS 6bp ins/ins frequency was significantly increased (OR 4,3; 95% CI of 1.58 to 11.7; p=0.003), whereas response to the treatment was associated with occurrence of TS 6bp allele del (HR OF 0.48; 95% CI of 0.23 to 1.0; p=0.049), of TSER 2R/3R (OR 0,32; 95% CI 0,12–0,88; p=0.042) and TS 6bp del/ins (OR 0.23; 95% CI 0.08–0.65; p=0.008) genotypes. We have not established statistically significant differences in the frequency of occurrence of haplotypes of the thymidylate synthase gene in RA patients with different therapeutic efficacy of MT, but we found a tendency to increase of the haplotype TS 3R-6bp del (OR 0.39; 95% CI 0.24–1.09; p=0.081) frequency in the «respondents» to the treatment.Conclusion. Our results may indicate the relationship of the thymidylate synthase gene single nucleotide polymorphisms with therapeutic response to MT in patients with RA.